2018
DOI: 10.1002/ptr.6116
|View full text |Cite
|
Sign up to set email alerts
|

The effect of topical piperine combined with narrowband UVB on vitiligo treatment: A clinical trial study

Abstract: Vitiligo is the most common acquired hypopigmentary disease in the community. Piperine as an herbal extract derived from black pepper has strong impact on the melanocyte proliferation and adverse side effects less than synthetic drugs such as corticosteroids. For the first time, this study was aimed to evaluate the effect of topical piperine combined with narrowband ultraviolet B (NB-UVB) on vitiligo treatment. In this double-blind clinical trial, 63 patients with facial vitiligo were randomly divided into 2 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 28 publications
0
16
0
1
Order By: Relevance
“…(1) e main power supply in the printed circuit board needs to be close to the ground plane, which is beneficial in shortening the power return path, reduce power loss, and reduce electromagnetic interference [11,12] (2) e high-speed signal layer must be close to the plane layer, preferably the ground plane layer, which can also shorten the return path, reduce signal attenuation, and have a shielding effect (3) e laminated design needs to be symmetrical to each other to avoid warping and deformation of the PCB board (4) e signal layer cannot be directly adjacent to each other; otherwise, it is easy to cause crosstalk and cause circuit function failure (5) Important signal lines need to be routed in the inner layer, preferably surrounded by two ground layers By consulting some common laminated design knowledge, and taking into account the practical application requirements of this article, in order to fully meet the electromagnetic compatibility and signal integrity of the video recorder of medical ultrasound equipment, this article uses a ten-layer PCB laminated structure to avoid the aforementioned inaccurate audio and video information due to factors such as immunity and sensitivity and also provide a guarantee for subsequent layout.…”
Section: Pcb Design and Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) e main power supply in the printed circuit board needs to be close to the ground plane, which is beneficial in shortening the power return path, reduce power loss, and reduce electromagnetic interference [11,12] (2) e high-speed signal layer must be close to the plane layer, preferably the ground plane layer, which can also shorten the return path, reduce signal attenuation, and have a shielding effect (3) e laminated design needs to be symmetrical to each other to avoid warping and deformation of the PCB board (4) e signal layer cannot be directly adjacent to each other; otherwise, it is easy to cause crosstalk and cause circuit function failure (5) Important signal lines need to be routed in the inner layer, preferably surrounded by two ground layers By consulting some common laminated design knowledge, and taking into account the practical application requirements of this article, in order to fully meet the electromagnetic compatibility and signal integrity of the video recorder of medical ultrasound equipment, this article uses a ten-layer PCB laminated structure to avoid the aforementioned inaccurate audio and video information due to factors such as immunity and sensitivity and also provide a guarantee for subsequent layout.…”
Section: Pcb Design and Implementationmentioning
confidence: 99%
“…. (12) e use of the mutual information method for registration is based on the following assumption: when two images are perfectly aligned, the total amount of information they contain should be the largest; that is, the mutual information is the largest. It can be seen from the above formula that maximizing mutual information and minimizing joint entropy are essentially the same.…”
Section: Measurement Criteriamentioning
confidence: 99%
“…Two clinical trials have evaluated the effect of topical piperine on vitiligo treatment and found positive effects (Table 2). In patients with facial vitiligo, topical treatment with piperine combined with narrowband UVB (NB-UVB) therapy resulted in significantly higher repigmentation rate at time intervals of 1, 2, and 3 months after treatment than in the control group [182]. In another study [183], a Piper nigrum fruit extract and pure piperine were integrated into different ointments and applied for 12 weeks to different skin areas of the vitiligo patients.…”
Section: Vitiligomentioning
confidence: 99%
“…The clinical trials completed are 11 and in addition that are currently ongoing are 5; a total of 1002 articles have been published on piperine in the last 10 years (Table 2 and Fig. 2 ) [ 12 15 ]. However, some of the clinical trial data is published but not registered.…”
Section: Introductionmentioning
confidence: 99%